2012
DOI: 10.1016/j.eplepsyres.2011.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of oxidative stress and mitochondrial function by the ketogenic diet

Abstract: The ketogenic diet (KD) is a high-fat, low carbohydrate diet that is used as a therapy for intractable epilepsy. However, the mechanism(s) by which the KD achieves neuroprotection and/or seizure control are not yet known. The broad efficacy of the KD in diverse epilepsies coupled with its profound influence on metabolism suggests that mitochondrial functions may be critical in its mechanism(s) of seizure control. Mitochondria subserve important cellular functions that include the production of cellular ATP, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
105
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(119 citation statements)
references
References 80 publications
4
105
0
2
Order By: Relevance
“…In addition to enhancing energy reserves, ATP levels, and the expression of many enzymes involved in multiple metabolic pathways in the mitochondria, the KD has also been shown to increase mitochondrial biogenesis in the hippocampus ( 48 ). Additionally, multiple studies have demonstrated elevated antioxidant activity, diminished production of ROS, and decreased ROS-induced damage with the KD ( 6,14,94 ). Figure 3 summarizes the substrates and pathways linking mitochondrial redox changes to the TCA and astrocytes from Bad Ϫ / Ϫ or Bad S155A mice exhibited reduced mitochondrial oxidative metabolism of glucose, but enhanced mitochondrial respiration in the presence of BHB ( 87 ).…”
Section: Bioenergetic and Mitochondrial Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to enhancing energy reserves, ATP levels, and the expression of many enzymes involved in multiple metabolic pathways in the mitochondria, the KD has also been shown to increase mitochondrial biogenesis in the hippocampus ( 48 ). Additionally, multiple studies have demonstrated elevated antioxidant activity, diminished production of ROS, and decreased ROS-induced damage with the KD ( 6,14,94 ). Figure 3 summarizes the substrates and pathways linking mitochondrial redox changes to the TCA and astrocytes from Bad Ϫ / Ϫ or Bad S155A mice exhibited reduced mitochondrial oxidative metabolism of glucose, but enhanced mitochondrial respiration in the presence of BHB ( 87 ).…”
Section: Bioenergetic and Mitochondrial Changesmentioning
confidence: 99%
“…However, it is important to recognize that much of the data discussed herein remain preliminary in nature. Nevertheless, the therapeutic potential for dietary therapies for neurological disorders remains almost limitless when viewed from the perspective of salvaging neuronal bioenergetic dysfunction ( 6,8,14 ).…”
Section: Effi Cacy In Epilepsy: Clinical Studiesmentioning
confidence: 99%
“…Mitochondria do not only supply cells with energy; they control the apoptosis, calcium levels and production and elimination of reactive oxygen species (ROS) (Milder et al, 2012). Nutrition based therapies are not only an option for rare mitochondriopathies but also for a spectrum of ND associated with aging (Procaccio et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Both roles make KB highly neuroprotective agents (Cahill, 2006). KB mediate their antioxidative properties by activation of protective transcription factors (like Nrf2) that increase the production of antioxidants like glutathione and other enzymes (Milder et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…diet profoundly alters redox processes, in part by increasing cellular glutathione levels via activation of the Nrf2 pathway (5,6). Therefore, a clear rationale exists for validating the Nrf2 pathway as antiepileptic or antiepileptogenic therapies.…”
mentioning
confidence: 99%